Easy dog food recipes : 60 healthy dishes to feed your pet safely - Shanahan, Scott (Rockridge Press, 2020)
Paws-itively easy and healthy dog food recipes-bone appetit! Dogs aren't just friendly pets, they're beloved family-and like any family member, the food you feed your pup needs to be healthy, high quality, and wholly delicious. Packed with simple recipes using fresh ingredients and straightforward advice on the best foods for your best friend, Easy Dog Food Recipes shows you how to ditch the store-bought kibble for balanced homemade meals you can trust. Become a home chef for your happy hound! Easy Dog Food Recipes gives you a look at the many benefits of healthy, homemade dog food, including a detailed breakdown of the vitamins and minerals every canine needs. Explore the best, budget-friendly ingredients for your DIY dog food, as well as advice for avoiding ingredients that can cause harm, before trying your hand at dozens of dog food recipes for howling good treats, meats, sauces, and more. Easy Dog Food Recipes includes: Canine cuisine-60 drool-worthy, nutrient-rich recipes will have your dog barking bow WOW for easy-to-make chow, such as Pumpkin Cookies, Shrimp and Quinoa, Turkey Pan Gravy, and more! Dog whisperer-Easy Dog Food Recipes offers proven advice leads you through the safest or most harmful ingredients, a guide to deciphering dog food labels, and mealtime training tips. Doggo diagrams-Super easy, scannable charts give you the lowdown on info such as accurate serving sizes for your pooch-from the tiniest Chihuahua to the most massive Mastiff-and how to serve a balanced bowl. From can to pan-your pup will woof their way through these hearty and healthy dog food recipes.